Misinterest Essays, Pensées, and Dreams - Bowker, M.H (punctum books, 2019)
"The term "interest" lacks a precise antonym. In English, we have "disinterested" and "uninteresting," but we want for a term that denotes robust opposition to interest. The same appears to hold true in every other language (as far as we know). Interest's missing antonym reflects not merely a widespread lexical oversight, but a misrecognition of interest's complete and exact meaning. More importantly, the idea that interest has no opposite expresses a certain refusal to acknowledge the power of the impulse to extinguish interest, for the self and for others. Why then do we foreclose interest's possibility, degrade our (and others') capacities to experience interest, and destroy interest's objects? Why do we decline what interest proffers - which includes creative and subjective being, thinking, and relating - in favor of more primitive modes of survival, thoughtlessness, and nonbeing? Why do relationships - with ourselves, with others, with objects - toward which genuine interest draws us seem sometimes, if not often, unbearable? These questions are difficult. Their answers, even more so. Misinterest: Essays, Pensées, and Dreams attempts to approach them in an honest way, without making them fascinating, mysterious, boring, obscurantist, or fascinatingly mysteriously boringly obscurantist. Outwardly, Misinterest is concerned with dreams and forgetting and Eros and soaring dogs and groups and suicidal suburban teenagers and sex and jury duty and Nazis and fathers and hatred and holy parrots and fundamentalists and plagues and other things that may or may not be interesting. Ultimately, however, it seeks, like Jules Renard, "en restant exact" (in remaining true/real), to shed light on the establishment of misinterest, missingness, and mystery where and when they need not be, and, thus, on the psychic, familial, and political forces that compel us not to be when and where we ought."